Cultivating Religious Character in Students Through the Storytelling Method About the Morals of the Prophet Muhammad SAW at SDN 88 Loka, Enrekang Regency - Pina Pina; Amir Patintingan; Muhammad Nur Maallah; M. Nasri Hamang; Andi Fitriani Djollong (Journal of Education and Learning Sciences, 2026)
Religious character education has become a strategic priority in elementary education, particularly within Islamic educational contexts where moral values are expected to be integrated into daily learning. Storytelling about the exemplary character of Prophet Muhammad (peace be upon him) is considered an effective pedagogical approach to fostering students' religious values through meaningful and contextual learning experiences. This study aimed to examine the implementation of the storytelling method in cultivating students' religious character at SDN 88 Loka Enrekang, Indonesia. A qualitative case study approach was employed over a three-month period. Data were collected through non-participant observations, semi-structured interviews with the principal and teachers, and document analysis. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while trustworthiness was ensured through source triangulation and methodological triangulation. The findings revealed that storytelling effectively strengthened students' understanding and practice of religious values, particularly honesty, patience, compassion, responsibility, and justice. Students demonstrated greater engagement in learning and showed positive behavioral changes after participating in storytelling activities. The effectiveness of the method was supported by teachers' enthusiasm, the creative use of visual learning media, and a conducive classroom environment. However, several challenges remained, including limited instructional time, inconsistent implementation across grade levels, and the limited availability of age-appropriate storytelling materials. Overall, the study concludes that storytelling centered on the moral virtues of Prophet Muhammad is an effective strategy for promoting religious character development while simultaneously enhancing students' moral awareness, learning motivation, and social behavior. These findings provide practical implications for strengthening character-based Islamic education in elementary schools.